Temporal Foraging and Ranging Patterns Suggested the Niche Partitioning of Two Sympatric Herbivores, Axis axis and Bubalus bubalis, in the Nijhum Dweep National Park of Bangladesh - Aftab Hossain; Syeda Ismat Ara; Biswajit Nath; Kazi Fayzatul Zannat; Md. Farid Ahsan (International Journal of Zoology)
For proper conservation measures and to elucidate coexistence mechanism of sympatric herbivore, we assessed the temporal foraging and ranging patterns of the Axis axis (spotted deer) and feral and/or semi domesticated Bubalus bubalis (buffalos) in the Nijhum Dweep National Park (NDNP) of Bangladesh. We have collected the data by day long scan sampling method for 12 months. We found that spotted deer and buffalos, respectively, spent 50.34% and 36.41% of their total day time in foraging. To avoid clash with the larger sized buffalos in the grazing ground, the spotted deer choose a slightly different time for grazing. At least three foraging peaks were found for spotted deer, whereas, buffalos showed two foraging peaks in a day. More importantly, spotted deer relied more on browsing for their food collection although they are natural gazer, whereas, buffalos relied more on their natural grazing habit for food collection. Spotted deer spent most of their time inside the forest and forest edges, whereas, buffalos mostly spent their time in the open grazing grounds. The range of total distance moved (TDM) per day for spotted deer and buffalos was 1.56 to 2.67 km and 1.02 to 3.30 km, respectively. The total area ranged (TAR) per day were 0.23 km2 to 0.8 km2 for spotted deer and 0.03 km2 to 0.35 km2 for buffalos. Although, these two parameters varied seasonally for both species, only in case of TAR of spotted deer the variation was statistically significant (P<0.05). We conclude that because of the presence of a larger sympatric herbivore, the spotted deer did some alterations in their temporal foraging and ranging pattern (TFRP) to survive in the small island which has very limited resources for their existence and survival.